Correlation between DLGAP5 expression in pancreatic ductal adenocarcinoma tissue and patient prognosis - ZHANG Wenjiao, XIE Fangyu, ZHANG Weiwei, FU Lailin, LYU Mei, LIU Jingyi, HAO Mingxing, XIE Xiangjun (精准医学杂志)
Objective To measure the expression of discs large-associated protein 5 (DLGAP5) in pancreatic ductal adenocarcinoma (PDAC) tissue, and to analyze its correlation with clinicopathological features and patient prognosis. Methods A total of 75 patients with PDAC who underwent surgical resection in Qingdao Municipal Hospital from September 2018 to December 2022 were selected. Immunohistochemical (IHC) staining was used to measure the expression of DLGAP5 protein in tumor and adjacent normal tissues. Patients with positive DLGAP5 expression were divided into low and high DLGAP5 expression groups according to DLGAP5 expression levels. The correlation between clinicopathological features and DLGAP5 expression levels was analyzed. A multivariate Cox regression model was used to analyze the prognostic risk factors in patients with positive DLGAP5 expression. A Kaplan-Meier survival curve was plotted to analyze the relationship between DLGAP5 expression levels and survival rates in these patients. Results IHC staining showed significantly higher expression DLGAP5 levels in PDAC tumor tissues than in adjacent normal tissues (χ2=36.930, P<0.05). Clinical data analysis showed significant differences between the low and high DLGAP5 expression groups in tumor differentiation, T stage, lymph node metastasis, and American Joint Committee on Cancer stage (χ2=6.222-10.940, P<0.05). Multivariate Cox regression model analysis showed that high DLGAP5 expression was an independent risk factor for poor prognosis in patients with positive DLGAP5 expression. The Kaplan-Meier survival curve showed that the cumulative survival rate was significantly lower in patients with high DLGAP5 expression than in those with low expression (χ2=18.929, P<0.05). Conclusion DLGAP5 is highly expressed in the tumor tissues of patients with poorly diffe-rentiated PDAC, stage T3+T4 tumor, lymph node metastasis, and stage Ⅱ+Ⅲ tumor. High DLGAP5 expression correlates with the poor prognosis in patients with PDAC. DLGAP5 shows promise as a new biomarker for PDAC diagnosis and prognosis.